Perceptions of family functioning in adolescents who self‐harm. Issue 2 (15th January 2015) - Palmer, Elizabeth; Welsh, Patrick; Tiffin, Paul Alexander
Abstract : This study compares the self‐reported family functioning of 21 adolescents presenting at four UK medical wards with self‐harming behaviour with those obtained from a sample of adolescents drawn from the local community. Adolescents hospitalized for self‐harm reported that their families were more dysfunctional than healthy controls on the family perceptions scale. However, this difference was not observed when covariates such as emotional and behavioural distress were controlled for. Poor levels of agreement between adolescents and adult family members in relation to family perceptions were also observed. The findings suggest that adolescents who engage in significant self‐harm perceive impairments in their family functioning. These reported impairments may be the result of concurrent emotional and behavioural distress or some form of interaction between family functioning and distress. A comprehensive family assessment to detect absolute changes and disparities in perceived family functioning may therefore help guide family interventions in this context. Practitioner points: Adolescents who are hospitalized for self‐harm report significant impairments in family functioning compared with healthy controls. Adolescent and adult family members appear to disagree on the degree of impaired family functioning. A comprehensive family assessment may therefore help guide family interventions in hospitalized adolescents.